ANALYSIS OF LUGGEST TB PATIENTS DRUG COMPLIANCE LEVEL IN GENERAL HOSPITAL CUT MEUTIA NORTH ACEH DISTRICT IN 2020 - ira, irawati (Jurnal Kajian Kesehatan Masyarakat, 2021)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Factors that influence a person to recover from his illness can be divided into three, namely individual factors, from outside the individual, and factors of religiosity. The indicator used to evaluate TB treatment is the Success Rate (SR). The purpose of this study was to analyze the level of compliance of pulmonary TB patients in taking medication at the Cut Meutia General Hospital, North Aceh Regency in 2020. This type of research was conducted using a qualitative approach. The sampling technique in this study was to use informants from health workers and TB patients. The main data collection technique in this study was carried out through in-depth interviews or in-depth interviews. Data analysis in this study used univariate, bivariate analysis. The results of the analysis of some informants who were categorized as cured and complete treatment obeyed and listened to every advice, recommendation, and instructions given by health workers. It is hoped that patients will be more obedient in undergoing treatment until the treatment phase is complete and do not stop TB treatment if they feel cured because the TB germs in the body have not completely died, even drug resistance or resistance can occur so that TB treatment will take longer.